Водні об'єкти Луцька: гідрографія, локальний моніторинг, водопостачання та водовідведення - Забокрицька, Мирослава Романівна; Хільчевський, Валентин Кирилович; Zabokrytska, Myroslava R.; Khilchevskyi, Valentyn K. (Київський національний університет імені Тараса Шевченка, 2016)
Was made the analysis of hydrographic network in the city Lutsk. Hydrological and hydrochemical characteristics of Styr river and its tributaries – mall rivers Sapalayivka, Omelyanyk and Zhyduvka was presented. It has been characterized quality of drinking water in the city Lutsk.
Water bodies of Lutsk: hydrography, local monitoring, water supply and water disposal
Keywords: річки; Стир; Сапалаївка; Омеляник; Жидувка; rivers; Styr; Sapalayivka; Omelyanyk; Zhyduvka